KEKUATAN PEMBUKTIAN ALAT BUKTI ELEKTRONIK DALAM PERADILAN PIDANA E-LITIGASI BERLANDASKAN NILAI KEADILAN - Nadya Widiawati; Achmad Solikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
There are problems applying the principles contained in the Criminal Procedure Code, where the emergence of the Corona Virus Disease 2019 or Covid-19 at the end of 2019 had a major impact on the world. This virus has claimed many lives in Indonesia, which has the highest number of infected and dead in Southeast Asia. The Covid-19 virus itself, according to the World Health Organization (WHO) is transmitted through one of them through droplets of people who have been infected which cause obstacles in a number of face-to-face activities, one of which is in terms of law enforcement in Indonesia. Along with the development of this virus which has not shown a decline, the three finally had time to make a Memorandum of Understanding (MoU) contained in the cooperation agreement between the Supreme Court of the Republic of Indonesia, the Attorney General's Office of the Republic of Indonesia, the Ministry of Law and Human Rights of the Republic of Indonesia Number: 402/DJU/HM.01.1 /4/2020, Number : KEP-17/E/Ejp/04/2020, Number : PAS- 08.HH.05.05 Year 2020 concerning the Implementation of Trials Through Teleconference. As a result of this MoU, there is a change in the procedural law process in court. The development of the E-Court, which so far has only been limited to serving the administration of cases electronically by adding electronic services, has received legal protection based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2019 concerning the Administration of Cases and Trials in Courts Electronically. E-court is a court instrument as a form of service to the community in terms of registering cases simultaneously with evidence in electronic courts, so if we refer to the criminal law of proof in a case, the existence of online or other names called E-Litigation is not in accorkemudiance with the theory of justice, where the theory of justice itself according to Aristotle understands justice in understanding equality